(3GdeSJWQa ef cd af eSJXQas - (3LeGd GdOjf eMeO Hf CMeO GdNWjH GdGHTjgjs ((3TjN eMeO Ydi s)
(3ChdgG (B:s
(3GdMeO ddg Gdedc GdYXje CeG HYO abO QCjJ LeGYI ef Phi Gdgee , LeYhG CTjGA cKjQI ef GdBOGH hGdMce , hHSWhG eLdOGJ a GdJhGQjN hGdfhGOQ hGdCNHGQ aGSJNQJ Gddg hLeYJ ef eLehYgG gPG GdeLehY GddWja s
(3BNQgG (B:s
(3BNQg ai BNQ GdHGH GdQGHY hGdKeGfjf ai aVd GdUdGI Ydi QShd Gddg Udi Gddg Ydjg hSde hgh BNQ GdCHhGH (B:" (3Gddge ELYdfG ef CeJg , hGMTQfG ai ReQJg hUdi Gddg Ydi SjOfG eMeO NGJe GdCfHjGA hGdeQSdjf hBdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI CNQis
(3Ydi ghGeTgG JUMjMGJ s
(3cJHJ YfGhjjf GdCHhGH hHYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs